The Covenants of the Prophet Muhammad: From Shared Historical Memory to Peaceful Co-Existence, By Ibrahim Mohamed Zein and Ahmed El-Wakil Routledge - Negoiță, Octavian-Adrian (Journal of the American Academy of Religion, 2025)
The Covenants of the Prophet Muhammad: From Shared Historical Memory to Peaceful Co-Existence offers a detailed exploration of crucial historical documents